Endoglin in head and neck neoplasms - Litwiniuk-Kosmala, Małgorzata; Makuszewska, Maria; Czesak, Małgorzata (Frontiers in Medicine, 2023)
Tumours of the head and neck region form a heterogenous group of pathologies, including various benign lesions and malignant neoplasms. Endoglin, also known as CD105, is an accessory receptor for transforming growth factor beta (TGF-β), that regulates angiogenesis, both in physiological as well as pathological conditions. It is highly expressed in proliferating endothelial cells; therefore it is considered as a marker for tumour-related angiogenesis. In this review we discuss the role of endoglin as a possible marker of tumorigenesis, as well as a potential target for antibody-based therapies in neoplasms of the head neck region.